Explaining the Duterte administration’s appeasement policy on China: The power of fear - De Castro, Renato Cruz (Animo Repository, 2019)
This article examines the reason behind the dramatic shift in Philippine foreign policy under the Duterte Administration. His predecessor, president Benigno Aquino, vigorously challenged China’s expansive territorial claim in the South China Sea throughout his six-year term. However, president Rodrigo Duterte’s actions and pronouncements are undoing the former president’s geopolitical agenda of balancing China’s expansion in the disputed waters. He distances the Philippines from the United States, its long-standing treaty ally, and gravitates toward China. This stance aims to earn goodwill with China so that the Philippines can avail itself of enormous aids and loans from China’s Belt and Road Initiative (BRI). This stemmed from this administration’s fear that the Philippines would not benefit from China’s emergence as an economic power. Nevertheless, by appeasing an expansionist power, the Philippines becomes complicit to China’s long-term strategy of maritime expansion to push the United States out of East Asia. In conclusion, the article warns that the Duterte Administration might end up losing the country’s exclusive economic zone (EEZ) in the South China Sea and the confidence and trust of its allies and security partners. This administration might also leave the public coffers empty and dry because of China’s reneging on its commitment to fund the Philippines’ massive infrastructure-building program, labeled “Build, Build, and Build.”. © 2019 Taylor & Francis Group, LLC.